Catheter-directed thrombolysis for in situ pulmonary artery thrombosis in children - Evyatar Hubara; Sharon Borik; Gili Kenet; David Mishaly; Amir Vardi (Wolters Kluwer Medknow Publications, 2021)
In situ pulmonary artery thrombosis (ISPAT) is a unique form of pulmonary embolism characterized by local formation of thrombus in the pulmonary arteries. We present here a baby with hypoplastic left heart syndrome who developed ISPAT after Glenn surgery. The patient underwent catheter-directed thrombolysis, followed by systemic anticoagulation with excellent results.